Comparative study of the sena’s regional valle training programs for the fruit-harvesting production chain, compared with a national and international reference - Recalde Rincones, Víctor Huver (Revista Colombiana de Investigaciones Agroindustriales, 2014)
This paper makes a comparison of the amount of performance areas attended by the different training programs of: operators, technicians and technologists of the Regional Valle SENA, for the qualification of the workers on the fruit-harvest production chain of the Valle del Cauca and the ones of Cundinamarca and Spain. For the comparison the EMBRAPA method was used, which proposes a comparative study selecting a national and international reference, therefore the SENA Cundinamarca program was selected as a national reference, and the Spain program as an international one. In the operator training programs a gap is found, in Spain the offer is of seven (7) while in the Valle del Cauca and in Cundinamarca the offer is of zero (0) in all the security and environment program levels, as well as the chemical area at technologist level, in biotechnology related topics. Compared to the national reference Cundinamarca, the situation is equal in the offerings of programs in the Chemical and Food Safety area at technic and technologist level, highlighting biotechnology topics. Para citar este artículo Recalde, V. (2014). Estudio comparativo de los programas de formación del SENA Regional Valle para la cadena hortofrutícola, comparados con un referente nacional e internacional. Revista colombiana de investigaciones agroindustriales, 1(1), 63-71. DOI: http://dx.doi.org/10.23850/24220582.116